2020
DOI: 10.1136/bmjgh-2020-002393
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of substandard, falsified, unlicensed and unregistered medicine sampling studies: a focus on context, prevalence, and quality

Abstract: Substandard and falsified (SF) medicines are a global issue contributing to antimicrobial resistance and causing economic and humanitarian harm. To direct law enforcement efficiently, halt the spread of SF medicines and antimicrobial resistance, academics, NGOs and government organisations use medicine quality sampling studies to estimate the prevalence of the problem. A systematic review of medicine quality studies was conducted to estimate how the methodological quality of these studies and SF prevalence has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 42 publications
0
45
1
1
Order By: Relevance
“…As correctly stated by McManus and Naughton, 5 the results of systematic reviews are only as reliable as the original data to which they refer. If the arbitrary choice of tolerance limits allows the rate of OOS medicines in the same study to vary by a factor of more than 10 (as shown in Figure 2 ), the results of systematic reviews obviously become unreliable, and, for example, comparisons of the rates of OOS medicines between different time periods, as attempted in the systematic review by McManus and Naughton, 5 may become meaningless.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…As correctly stated by McManus and Naughton, 5 the results of systematic reviews are only as reliable as the original data to which they refer. If the arbitrary choice of tolerance limits allows the rate of OOS medicines in the same study to vary by a factor of more than 10 (as shown in Figure 2 ), the results of systematic reviews obviously become unreliable, and, for example, comparisons of the rates of OOS medicines between different time periods, as attempted in the systematic review by McManus and Naughton, 5 may become meaningless.…”
Section: Discussionmentioning
confidence: 96%
“…As correctly stated by McManus and Naughton, 5 the results of systematic reviews are only as reliable as the original data to which they refer. If the arbitrary choice of tolerance limits allows the rate of OOS medicines in the same study to vary by a factor of more than 10 (as shown in Figure 2 ), the results of systematic reviews obviously become unreliable, and, for example, comparisons of the rates of OOS medicines between different time periods, as attempted in the systematic review by McManus and Naughton, 5 may become meaningless. Given the important public health and socioeconomic effects of SF medicines, and the importance of reliable and comparable prevalence data for such medicines, a harmonization of the tolerance limits used to distinguish compliant from OOS products in different medicine quality studies is urgently called for, as also concluded from a recent study by the Brazilian Health Regulatory Agency.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations